The Relationship Between Preschool Teachers' Professional Ethical Behavior Perceptions, Moral Judgment Levels and Attitudes to Teaching - RAMAZAN, MÜSLİMAT OYA (SAGE Publications Ltd, 2010)
Morality is the stance and attitude that makes a social human being; the display of behaviors such as praise, criticism, tolerance and intolerance, confirmation and rejection; the taking of sides by stating what one finds good or bad, right or wrong, instead of staying indifferent to what other people say and do (Pieper, 1999). Moral development needs to be taught at schools from the personality-shaping years of preschool so as to raise individuals with a strong sense of morality. Teachers are as important as families in children's moral development. Although parents may play a crucial role in child development within the family environment, once children start school, teachers take the primary importance in children's lives. As pointed out by Dewey (1995), telling preschool children to behave morally has very little contribution towards the development of moral behavior. Therefore, it is of utmost importance that teachers involved in morality education act as models for children by displaying ethical and moral behavior. As a discipline, morality is the collection of ethical codes reflected in practical everyday life; they constitute the value system guiding a society's behaviors, attitudes and beliefs. In their studies, Oser (1991) and Terhart (1998) state that teachers' professional quality depend on the development of cognitive, moral and practical domains, and that these three together define teacher competencies. Therefore, it is not enough for teacher education programs to improve teachers in only one domain; moral judgment levels and teaching attitudes play a determining role in the identification of teacher ethical behaviors. Starting from this, the present study investigates the relationship between preschool teachers' professional ethical behavior perceptions, moral judgment levels and teaching attitudes. The sample includes 464 randomly selected preschool teachers working in 10 different regions of Istanbul. Three different measurement tools were used: Preschool Teacher Ethical Behaviors Scale, Moral Judgment Test, and Teaching Attitudes Scale. The results seem to imply that a linear relationship exists between the variable of ‘preschool teachers’ ethical behavior perceptions’ and the variables of ‘moral judgment level’, ‘democratic attitude’, ‘autocratic attitude’ and ‘apathetic attitude’. Put differently, preschool teachers' perceptions about ethical behaviors are predicted by moral judgment level, democratic attitude, autocratic attitude and apathetic attitude. © 2010 A B Academic Publishers Printed in Great Britain.